Comparative Effects of High-Intensity Interval Training (HIIT) and Moderate-Intensity Continuous Training (MICT) on Cardiac Peroxisome Proliferator-Activated Receptor Gamma Coactivator 1-Alpha (PGC-1α) and Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2) mRNA Expression in Wistar Rats - Amalia Prarizkahati; Nova Sylviana; Hanna Goenawan (Global Medical & Health Communication (GMHC), 2025)
Sedentary behavior increases cardiovascular disease (CVD) risk through oxidative stress and mitochondrial dysfunction. Exercise modalities such as moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT) may counter these effects by regulating peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) and nuclear factor erythroid 2-related factor 2 (Nrf2). This experimental study compared the effects of MICT and HIIT on myocardial mRNA expression of PGC-1α and Nrf2 in male Wistar rats. Eighteen rats were randomly allocated to control, MICT, or HIIT groups (n=6) and underwent 8 weeks (January–April 2025) of treadmill training at the Animal Research Innovation Central (ARIC) and Central Laboratory of Universitas Padjadjaran, Sumedang, Indonesia. Myocardial mRNA expression was assessed using quantitative PCR and analyzed with one-way ANOVA (p<0.05). PGC-1α expression increased in both exercise groups versus control (0.498±0.139), with higher levels in MICT (0.921±0.094) and HIIT (0.839±0.073), corresponding to 1.8- and 1.7-fold increases, without a significant difference between the two (p=0.556). Nrf2 expression showed a mild, nonsignificant increase in MICT (0.708±0.110) and HIIT (0.682±0.171) compared to control (0.651±0.097; p=0.923). In conclusion, both MICT and HIIT enhance myocardial mitochondrial biogenesis by upregulating PGC-1α, supporting their cardioprotective effects, while unchanged Nrf2 expression may reflect redox homeostasis during chronic exercise.